Supporting Pesantren-based Higher Education to Internalize Value Education - Siswati, Vialinda; Abidin, Zainal; Zaldi, Ahmad (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
The value of education has long been used at pesantren (Islamic boarding schools) in Indonesia. The present research discusses implementing value education practices and developing students' interpersonal awareness in the context of pesantren-based higher education. The research employed a qualitative method by adopting a case study design in which data gathering methods included observation, interviews, and documentation. The data analysis technique utilizes the data analysis framework. The sources of this research are Universitas Islam Internasional Darullughah Wadda'wah and Universitas Darussalam Gontor East Java. The results show that implementing value education in pesantren-based higher education is deeply entrenched in religious and prophetic values. These values encompass various elements, including kiai (local Islamic leaders), santri (Islamic students), boarding schools, teachers, books, mosques, and campuses, collectively forming an integral part of the value framework. Islamic boarding schools' educational practices and regulations exhibit principles such as honesty, simplicity, independence, purity of heart, and dedication. Furthermore, these principles are instilled through habits, supervision of students, religious discussion sessions, and a range of additional efforts to shape these values within the students' souls and characters.